Learning Strategy Development for Solving Non-routine Problems Through 5E Model in Mathematics Learning: A Proposal - Shawan, Muslimah; Osman, Sharifah; Salleh Abu, Mohd; Fadzil Daud, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to develop a learning strategy of solving non-routine problems to overcome the difficulties that students face in problem-solving. The methodology of design and development research pioneered by Richey and Klein [1] was applied using three phases of the study. The data of the first phase needs analysis was obtained by administering tests and conducting interviews with students who had difficulty in solving non-routine problems. The research data will be thematically analyzed, including open coding and axial coding that will generate themes. Next, the data on the design and development stages will be collected using the Fuzzy Delphi technique. Data from expert interviews will be transcribed and coded to generate themes for developing the questionnaire that will be answered by 30 experts in mathematics, including those interviewed earlier. The analysis is based on expert responses to the questionnaire using the fuzzy linguistic Likert scale. Threshold value 'd' will be calculated to obtain expert consensus on all items included in the questionnaire. The third phase uses a quasi-experimental method to evaluate the effectiveness of the learning strategies developed. Two groups of 30 students each will be involved in this phase. A comparison of achievements between treatment and control groups will be performed through pre-test and post-test. This learning strategy will emphasize the social interactions of a student with peers or students with the teacher to find solutions. By using this strategy, students will be able to learn problem-solving better and improve their problem-solving skills.